Diagnosis of a duodenal-colonic cyst with inflammatory content derived of a metastatic gallbladder adenocarcinoma: a case report - Vargas-García, Elsa K. (2022)
The existence of a cystic mass which walls originated from a metastatic gallbladder adenocarcinoma is infrequent. We present the case of 68-year-old male that present to the emergency department with abdominal distention, hyporexia and jaundice. Upon exploratory laparotomy, a duodeno-colonic cyst with walls formed by metastatic cells derived from a Gallbladder Adenocarcinoma. Metastatic disease from a gallbladder adenocarcinoma to transverse colon and duodenum formed adherences between both organs, leading to the formation of cystic mass. Cancer cells have multiple adaptation mechanisms in order to survive harsh environments.